Tingkat Pemahaman Mahasiswa Terhadap Manajemen Stres Dan Dampaknya Terhadap Kesehatan Mental - Akbar Syafruddin; Nur Indah Atifah Anwar; Ilham Aksir (Indonesian Journal of Physical Activity, 2025)
This study uses a quantitative approach with a descriptive research type. This approach was chosen to determine the level of students' understanding of stress management and its impact on mental health. This study was conducted at the Physical Education, Health, and Recreation Study Program, Makassar State University, with 50 active students as research subjects. The selection of respondents was carried out using a purposive sampling technique, where the main criteria set were active students who were willing to be respondents and did not have a history of severe mental disorders medically. The main instrument in this study was a closed questionnaire compiled based on indicators of understanding stress management and the impact of stress on students' mental conditions. Each item on the questionnaire used a Likert scale with 5 (five) answer choices. The results of the Cronbach's Alpha reliability test with a value of 0.951. The data analysis technique was carried out using a descriptive test which was then categorized using a category table. Based on the results of the research and data analysis, it can be concluded that the level of understanding of students in the Physical Education, Health, and Recreation Study Program, Makassar State University is in the moderate category. Keywords: Understanding, Stress Management, Mental Health, Students